Окремі аспекти розвитку функції прокуратури на стадії досудового розслідування - Обушенко, Олександр Миколайович; Обушенко, Александр Николаевич; Obushenko, Alexander N. (Одеса : Фенікс, 2014)
Досліджено теоретичні та законодавчі положення щодо окремих аспектів розвитку діяльності прокуратури на стадії досудового розслідування. На підставі проведеного дослідження надано пропозиції щодо визначення функції, яку повинна здійснювати прокуратура на стадії досудового розслідування.

Исследуются теоретические и законодательные положения в отношении отдельных аспектов развития деятельности прокуратуры на стадии досудебного расследования. На основании проведенного исследования обосновываются предложения по определению функции, которую обязана выполнять прокуратура на стадии досудебного расследования.

The article deals with the procedural status of prosecution under preliminary investigation. This procedural status is reflected in the right to carry out prosecution during the preliminary investigation of a particular function, which must comply with the Constitution of Ukraine and other laws of Ukraine. In the article analyzes the function of prosecution under preliminary investigation to meet the requirements of the Criminal Procedure Code of Ukraine of 1960 and the Criminal Procedure Code of Ukraine of 2012. There is the analysis of the scientists’ views on the prosecutor under preliminary investigation. The views of scientists on the prosecutor under preliminary investigation are different. Some scientists think that the prosecutor under preliminary investigation provides the prosecution as to his competence further includes executing state accusation. According to other scientists prosecutor under preliminary investigation has the right to perform a function of supervision. There is also the view and the possibility of combining the prosecutor supervisory functions and prosecution.
Обушенко О. М. Окремі аспекти розвитку функції прокуратури на стадії досудового розслідування / О. М. Обушенко // Актуальні проблеми політики : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), М. А. Польовий [та ін.] ; НУ «ОЮА», Південноукраїнський центр гендерних проблем. – Одеса : Фенікс, 2014. – Вип. 53. – С. 315-324.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; функції прокуратури; реформа українського кримінального судочинства; досудове розслідування; функции прокуратуры; реформа украинского уголовного судопроизводства; досудебное расследование